Potrait Empirical Performance Finance Banking Sharia in Indonesia: Systematic Literature Reviews - Novalia, Adinda Sandya; Nurhayati , Fitri; Marjohan, Masno (Indonesian Development of Economics and Administration Journal, 2025)
The aim of this study was to analyze the financial performance of Islamic banking using data collected from journals published between 2017 and 2021, applying a systematic literature review method. The findings from the review reveal the following: 1) A total of 31 articles were reviewed, with 11 articles published in 2017, 6 in 2018, 7 in 2019, 5 in 2020, and 2 in 2021; 2) Researchers predominantly employed a descriptive quantitative method using descriptive statistical approaches, with no studies utilizing qualitative or mixed-method approaches; 3) Financial ratios were the primary tools used for performance measurement; 4) The financial performance of Islamic banking was found to be volatile but generally showed an improving trend; 5) To enhance performance, Islamic banks are advised to improve their financial ratios; and 6) The study’s limitations include the sample size, number of variables and indicators, observation period, and analytical techniques used